1969
DOI: 10.1136/bmj.1.5642.498
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Emergencies in an Urban Borough

Abstract: Summary: An analysis is presented of all emergency calls made in one year, "out of hours," to local authority mental health social workers as part of a comprehensive psychiatric service in an urban community. Of 212 calls received, more related to men than women, and in both sexes the peak age group was 40 to 49 years; 72% of referrals were in the psychosis or personality disorder diagnostic groups. A minority of cases referred had symptoms of only recent onset, and 70% of all calls related to patients previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1970
1970
1979
1979

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Brown et al (1966) and Gleisner (1971) showed that doctors responded by admitting patients with behaviour disturbance more readily than patients with other symptoms, and Lawson (1966) showed that mental welfare officers requested admission more frequently if the patient was seen as an emergency during a crisis than if there was a delay before seeing the patient. In addition, Mountney et al (1969) and Mendel (1966) in America showed that inexperienced doctors admitted patients more readily than experienced doctors and these were the doctors dealing with the emergencies in this study. Thus the behaviour patterns which defined those patients who would be rapidly readmitted are those which other studies have shown resulted in the admission of patients to hospital.…”
Section: Discussionmentioning
confidence: 69%
“…Brown et al (1966) and Gleisner (1971) showed that doctors responded by admitting patients with behaviour disturbance more readily than patients with other symptoms, and Lawson (1966) showed that mental welfare officers requested admission more frequently if the patient was seen as an emergency during a crisis than if there was a delay before seeing the patient. In addition, Mountney et al (1969) and Mendel (1966) in America showed that inexperienced doctors admitted patients more readily than experienced doctors and these were the doctors dealing with the emergencies in this study. Thus the behaviour patterns which defined those patients who would be rapidly readmitted are those which other studies have shown resulted in the admission of patients to hospital.…”
Section: Discussionmentioning
confidence: 69%